2017
DOI: 10.1016/j.jtcvs.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A pilot goal-directed perfusion initiative is associated with less acute kidney injury after cardiac surgery

Abstract: Background We sought to determine whether a pilot goal-directed perfusion initiative could reduce the incidence of acute kidney injury after cardiac surgery. Methods On the basis of the available literature, we identified goals to achieve during cardiopulmonary bypass (including maintenance of oxygen delivery >300 mL O2/min/m2 and reduction in vasopressor use) that were combined into a goal-directed perfusion initiative and implemented as a quality improvement measure in patients undergoing cardiac surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 35 publications
0
63
0
3
Order By: Relevance
“…In fact, it has been reported that low oxygen delivery on bypass is an independent predictor of AKI in patients who undergo cardiac surgery . In a recent cardiac surgery study, Magruder et al showed that maintenance of oxygen delivery>300 mL/min/m 2 decreased the incidence of acute kidney injury stages 1, 2, and 3 when compared with matched controls . We decided to use the same cutoff value and found similar results; patients with a nadir oxygen delivery <300 mL/min/m 2 had increased risk of RRT after HT almost by threefold.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, it has been reported that low oxygen delivery on bypass is an independent predictor of AKI in patients who undergo cardiac surgery . In a recent cardiac surgery study, Magruder et al showed that maintenance of oxygen delivery>300 mL/min/m 2 decreased the incidence of acute kidney injury stages 1, 2, and 3 when compared with matched controls . We decided to use the same cutoff value and found similar results; patients with a nadir oxygen delivery <300 mL/min/m 2 had increased risk of RRT after HT almost by threefold.…”
Section: Discussionmentioning
confidence: 75%
“…They are also consistent with clinical observations that low pump flow or low whole body DO 2 on CPB is associated with greater incidence of postoperative AKI 9,22,23 and that avoidance of low whole body DO 2 during CPB can reduce the incidence of postoperative AKI. 10,11 Medullary PO 2 was also increased by low-dose infusion of metaraminol to increase MAP from w63 to w90 mm Hg.…”
Section: Discussionmentioning
confidence: 95%
“…8 However, there have been no systematic investigations of renal global and regional (i.e., cortical and medullary) perfusion and oxygenation in a clinically relevant large animal model of CPB. Furthermore, although evidence shows that goaldirected perfusion can mitigate risk of postoperative AKI [9][10][11] and that the increase in renal fractional oxygen extraction during CPB can be alleviated by increasing pump flow, 12,13 the potential for perfusion conditions to be…”
mentioning
confidence: 99%
“…GDT is associated with a reduction in the incidence of AKI, renal replacement therapy (RRT), ICU stay, and hospital stay, as well as decreased risk of renal dysfunction and reduced mortality [30] . Magruder et al [31] investigated the effects of goaldirected perfusion therapy on AKI in a pilot study where AKI incidence was 23.9% in control patients vs. 9.1% in the GDT group, indicating an association between reduced AKI and GDT.…”
Section: B Goal-directed Therapy (Gdt)mentioning
confidence: 99%